Analisis Papan Komposit Dari Bahan Dasar Tempurung Kluwak Dan Kulit Buah Aren Sebagai Pengganti Material Papan Kayu - Heri Suryaman; Abdullah Ammar; Ignatius Blaier; Dimas Kristian Rega Pramono; Dawam Mulia; Fitria Nova Dewi Suyono Putri (Jurnal Nusantara Berbakti, 2023)
The high level of development in Indonesia has led to the need for wooden boards, which can cause damage to the ecosystem due to the continuous cutting of trees in the forest. There is a need for alternative raw materials to replace wooden boards for building purposes. Kluwak shells and aren fruit peels were chosen as the main raw materials for making composite boards in this research activity because these materials are high in cellulose content. This research was conducted to determine the effectiveness of composite boards made from kluwak shells and aren fruit peels as a substitute for wooden boards for building purposes. The research data collection process used experimental methods, while the analysis and discussion process used descriptive-quanlitative methods. The results showed that aren fruit peels powder is less suitable for use as raw material for making composite boards, because the powder grains are too fine, making it difficult to be bound by the matrix. While kluwak shell powder is quite suitable to be used as raw material for making composite boards, because the powder grains are not too fine so they can be bound by the matrix